Lettering, Swastik Court - Ayan Ghosh (2023)
Bas relief panels exhibit tropical fauna, Swastik Court. The three-panel design on the front façade was originally made from colourcrete but had been plastered over during previous interventions. They were revealed during the latest restoration of the building.